1979
DOI: 10.1159/000153011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein and Red Cell Enzyme Groups among the Nepalese

Abstract: Nepalese blood samples were tested for two plasma proteins and seven red cell enzyme systems. Polymorphic variation was present for the haptoglobin protein system and for the acid phosphatase, phosphoglucomutase locus 1, adenylate kinase and 6-phosphogluconate dehydrogenase loci controlling red cell enzyme systems. Gene frequencies are compared between the eastern and western Nepalese tribes, and with the distribution pattern known in other South and South-East Asian population groups. The possible interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…A similar frequency of Tf c2 has been reported in other Mongoloid populations like Japanese (Beckman et al, 1980;Kamboh and Kirk, 1983b) and Chinese (Tan et al, 1982;Kamboh and Kirk, 1983b;Saha, 1985Saha, , 1987. The frequencies of Tf B and Tf DChi in the present Lepcha population are also similar to those in the Chinese, Japanese, Nepalese and Bhutanese (Beckman et al, 1980;Kamboh and Kirk, 1983b;Tan et al, 1982;Sunderland et al, 1979;Mourant et al, 1968;Glassgow et al, 1968). The frequencies of Tf alleles in the present Lepcha population is not very different from those reported in diverse groups of Indian populations (Saha, 1987;Saha and Tan, 1983;Kamboh and Kirk, 1983b;Reddy et al, 1984;Walter et al, 1981Walter et al, , 1983 Table 2 shows the distribution of observed and expected frequencies of different phenotypes and genes of the Gc alleles in the Lepchas according to their religion.…”
Section: Methodssupporting
confidence: 88%
“…A similar frequency of Tf c2 has been reported in other Mongoloid populations like Japanese (Beckman et al, 1980;Kamboh and Kirk, 1983b) and Chinese (Tan et al, 1982;Kamboh and Kirk, 1983b;Saha, 1985Saha, , 1987. The frequencies of Tf B and Tf DChi in the present Lepcha population are also similar to those in the Chinese, Japanese, Nepalese and Bhutanese (Beckman et al, 1980;Kamboh and Kirk, 1983b;Tan et al, 1982;Sunderland et al, 1979;Mourant et al, 1968;Glassgow et al, 1968). The frequencies of Tf alleles in the present Lepcha population is not very different from those reported in diverse groups of Indian populations (Saha, 1987;Saha and Tan, 1983;Kamboh and Kirk, 1983b;Reddy et al, 1984;Walter et al, 1981Walter et al, , 1983 Table 2 shows the distribution of observed and expected frequencies of different phenotypes and genes of the Gc alleles in the Lepchas according to their religion.…”
Section: Methodssupporting
confidence: 88%
“…An isolated case of PGM6-1 has been observed among the Christian Lepchas. Similar frequencies of PGM alleles have been observed in Nepalese [Sunderland et al, 1979;Mou rant et al, 1976] and in Bhutanese [Glas gow et al, 1968]. However, Bangham and Howarth [1980] have reported a lower fre quency of PGM1 (0.63) in Sherpas of Ne pal.…”
Section: Phosplioglucomutase (Pgm)supporting
confidence: 74%
“…Similar frequencies of the acid phosphatase alleles have been reported in different populations of Nepal [Sunderland et al, 1979] and Bhutan [Glasgow et al, 1968], A slightly higher frequency of pa has been reported in IndoNepalese tribes [Mourant et al, 1968], Tamang and Sherpa [Bangham and Howarth, 1980], Assamese [Goedde et al, 1972] and Bengalis [Das et al, 1970: Saha, in press]. A low frequency of has been reported among the Kiranti of Nepal, As sam, and Bengal.…”
Section: Acid Phosphatase (P)supporting
confidence: 54%
“…Regarding neighboring populations, the data for Iranians were taken from Ohkura et al [1984] and Kirk et al [1977], those for Afghans from Papiha et al [1972], those for the Sinhalese from Ro berts et al [1972a, b], Papiha [1973] and A beyaralne el al. [1975], those for the Nepalese from Bhasin [1970], Bird et al [1957], Sunderland et al [1979], Santachiara-Benerecelti et al [1976], those for the Bhuta nese from Mourant et al [1968], those for the Malay and Chinese populations from Mourant et al [1976] and Blake et al [1973], and those for the Bataks of Samosir Island, Sumatra, from Hawkins et al [1973] and McDermid et al [1973]. We used the gene fre quency data for the largest number of loci available for any population.…”
Section: Methodsmentioning
confidence: 99%